X-linked inhibitor of apoptosis protein (XIAP) predicts disease-free survival in BRAFV600E mutant papillary thyroid carcinoma in middle eastern patients - Parvathareddy, Sandeep Kumar; Siraj, Abdul K.; Bu, Rong; Iqbal, Kaleem; Al-Rasheed, Maha; Al-Haqawi, Wael; Annaiyappanaidu, Padmanaban; Siraj, Nabil; Ahmed, Saeeda O.; Al-Sobhi, Saif S.; Al-Dayel, Fouad; Al-Kuraya, Khawla S. (Frontiers in Endocrinology, 2022)
Background: X-linked inhibitor of apoptosis (XIAP) is the most potent caspase inhibitory IAP family member and its over-expression is implicated in aggressive behavior of various solid tumors, including papillary thyroid carcinoma (PTC). BRAFV600E mutation is the most common oncogenic event in PTC and is also known to be associated with aggressive clinico-pathological characteristics. In this study, we investigated the prevalence of XIAP expression in more than 1600 PTCs from Middle Eastern ethnicity and its prognostic value to predict disease-free survival (DFS), in combination with the BRAFV600E mutation. Methods: Clinical data, XIAP expression by immunohistochemistry and BRAF mutation status were analyzed in 1640 Saudi PTC patients seen at our institute between 1988 - 2020. Results: BRAFV600E mutation was found in 910 of 1640 patient (55.5%) and was significantly correlated with older age, extrathyroidal extension, bilaterality, multifocality and lymph node metastasis, but was not an independent predictor of DFS. XIAP was over-expressed in 758 of 1640 (46.2%) and was associated with aggressive clinico-pathological features. It was also found to be an independent prognostic marker for DFS (HR = 1.28, 95% CI = 1.02 – 1.60, P = 0.0342). XIAP overexpression was correlated with presence of BRAFV600E mutation in PTC patients. Interestingly, we found the ability to predict shorter DFS was 2.7-fold higher in PTCs with over-expression of XIAP and BRAFV600E mutation compared to patients with high XIAP and wild-type BRAFV600E status. (HR = 2.74, 95% CI = 2.19 – 3.44, p < 0.0001). Conclusion: XIAP expression is an independent predictor of prognosis in Middle Eastern PTC patients. Combination of XIAP expression and BRAFV600E mutation can synergistically improve the DFS prediction in PTC patients, which may help clinicians to establish the most appropriate initial care and long-term surveillance strategies.